Mass Spectrometry-Based Metabolomics Revealed Effects of Metronidazole on Giardia duodenalis - Supaluk Popruk; Amanee Abu; Sumate Ampawong; Tipparat Thiangtrongjit; Phornpimon Tipthara; Joel Tarning; Suthasinee Sreesai; Onrapak Reamtong (MDPI AG, 2023)
Giardia duodenalis is a significant protozoan that affects humans and animals. An estimated 280 million G. duodenalis diarrheal cases are recorded annually. Pharmacological therapy is crucial for controlling giardiasis. Metronidazole is the first-line therapy for treating giardiasis. Several metronidazole targets have been proposed. However, the downstream signaling pathways of these targets with respect to their antigiardial action are unclear. In addition, several giardiasis cases have demonstrated treatment failures and drug resistance. Therefore, the development of novel drugs is an urgent need. In this study, we performed a mass spectrometry-based metabolomics study to understand the systemic effects of metronidazole in G. duodenalis. A thorough analysis of metronidazole processes helps identify potential molecular pathways essential for parasite survival. The results demonstrated 350 altered metabolites after exposure to metronidazole. Squamosinin A and N-(2-hydroxyethyl)hexacosanamide were the most up-regulated and down-regulated metabolites, respectively. Proteasome and glycerophospholipid metabolisms demonstrated significant differential pathways. Comparing glycerophospholipid metabolisms of G. duodenalis and humans, the parasite glycerophosphodiester phosphodiesterase was distinct from humans. This protein is considered a potential drug target for treating giardiasis. This study improved our understanding of the effects of metronidazole and identified new potential therapeutic targets for future drug development.